Social Influence, Impulse Buying and Virtual Product Purchasing Behavior among Indonesian Millennials and Generation Z in Mobile Legends: Bang Bang - Tandias, Chairia Ananda; Asmara , Namira Citta (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to examine the determinants of purchasing behavior for virtual product shopping in Mobile Legends: Bang Bang among Indonesia Millennials and Generation Z, concentrating on the role of social influence as an independent variable, purchasing behavior as a dependent variable and impulsive buying as a mediator variable. Utilizing quantitative approach and positivism paradigm, 152 data was collected from respondents through an online survey and the data were then analyzed with SmartPLS 4.0 using PLS-SEM and Multi-Group Analysis (MGA). The findings demonstrate that purchasing behavior is significantly affected by social influence and mediated by impulse buying. While there are no significant differences between Millennials and Generation Z in terms of their purchasing behavior towards virtual in-game products, these findings highlight the importance of emotional and social factors on shaping customer purchasing behavior in virtual settings. Future research may extend this model of study by adding other contextual or psychological factors that may influence virtual product purchasing behavior.